O Brother, Where Start Thou? Sibling-Spillovers in College Enrollment - Joshua S. Goodman; Michael Hurwitz; Christine Mulhern; Jonathan Smith (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study within-family spillovers in college enrollment to show college-going behavior is transmissible between peers. Because siblings' test scores are weakly correlated, we exploit college-specific admissions thresholds that directly affect older but not younger siblings' college options. Older siblings' admissibility substantially increases their own four-year college enrollment rate and quality of college attended. Their improved college choices in turn raise younger siblings' college enrollment rate and quality of college chosen, particularly for families with low predicted probabilities of college enrollment. Some younger siblings follow their older sibling to the same campus but many upgrade by choosing other colleges. The observed spillovers are not well-explained by price, income, proximity or legacy effects, but are most consistent with older siblings transmitting otherwise unavailable information about the college experience and its potential returns. The importance of such personally salient information may partly explain persistent differences in college-going rates by income, geography and other characteristics that define a community.
Keywords: 330; college enrollment; peer effects; siblings; admissions; regression discontinuity